A Comprehensive Qualitative Review of Studies Evaluating the Impact of Local US Laws Restricting the Sale of Flavored and Menthol Tobacco Products. Issue 4 (15th September 2021) - Rogers, Todd; Brown, Elizabeth M; Siegel-Reamer, Leah; Rahman, Basmah; Feld, Ashley L; Patel, Minal; Vallone, Donna; Schillo, Barbara A
Abstract: Objectives: To assess the quality of evidence on the effectiveness of local US laws restricting the sale of flavored tobacco products. Methods: We conducted a systematic search and qualitative scoping review of English-language papers published through May 2020 that evaluated flavored tobacco sales policies implemented by US jurisdictions during 2010–2019. We constructed a conceptual model for flavored and menthol tobacco sales restriction outcomes, assigned GRADE quality of evidence ratings to policy outcomes evaluated through the included studies, and summarized factors that might explain weak or inconsistent findings. Results: We found moderate to high quality of evidence associating policy implementation with reduced availability, marketing, and sales of policy-restricted products, and decreased youth and adult tobacco use of these products; however, policy exclusions and exemptions, implementation challenges, tobacco industry actions (e.g., marketing of concept-named flavored products; exploiting policy exemptions for certain store types), and consumer responses (e.g., cross-border or illicit purchasing) might undermine or mitigate intended policy effects. Conclusions: Flavored and menthol tobacco product sales restrictions implemented and evaluated in US jurisdictions appear to have achieved some of their intended outcomes; however, deficiencies in study designs, methods, and metrics could contribute to equivocal findings on quality of evidence associating policy implementation and outcomes. Gaps in the evidence are beginning to be filled with research using more rigorous study designs, improved measurement and analytic methods, and longer-term follow-up. Implications: In the absence of comprehensive federal action, US jurisdictions have the obligation to restrict flavored and menthol product sales to protect vulnerable populations from tobacco-related harms. The considerable expenditure of financial resources, political will, and time dedicated to policy adoption and implementation argue for evaluation studies designed to maximize the quality of evidence. This review offers generalizable insights into evaluation findings that can inform efforts to enhance tobacco control policy implementation and impact in the US and globally.